Optimization of the Creative Economy in Improving the Welfare of Society from the Perspective of Islamic Economics - Achmad Faisal Hadziq; Noorma Yunia; Dedi Firdaus (Journal of Economy, Accounting and Management Science (JEAMS), 2023)
Creative economy is one of the new economic concepts that intensifies information, creativity, and human resources as the most important factors of production. The products produced from the creative economy are characterized by their uniqueness and distinctiveness. These products can also be a development of existing products. The formulation of the problem addressed in this study is how to optimize the creative economy in Bojong Menteng Village, how creative economic activities in Bojong Menteng Village can improve the welfare of the community, and what are the obstacles faced by the creative economy in improving welfare. The research aims to determine how to optimize the creative economy in Bojong Menteng Village, understand how creative economic activities in Bojong Menteng Village can improve the welfare of the community, and identify the obstacles faced by the creative economy in improving welfare. This research is a qualitative study with a case study approach aimed at understanding the role of creative economy in improving the welfare of the community in Bojong Menteng Village, Leuwidamar District, Lebak Regency. The data collection techniques used in this research include observation, interviews, documentation, and literature review. The results of the study show that optimizing the creative economy has had a positive impact on improving the welfare of the community in Bojong Menteng Village by providing employment opportunities. Although there have been only slight changes and not significant ones, the creative economy has been able to enhance the welfare of the community through job opportunities and reducing unemployment rates.